2011
DOI: 10.33736/jcest.90.2011
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Acacia Mangium in Structural Size at Green Condition

Abstract: Acacia mangium is one of the most popular choices in the reforestation and rehabilitation of abandoned shifting cultivation areas dated back to the 70's. This paper looks into the evaluation of mechanical strength and physical properties in structural size at green condition for Acacia mangium. The mechanical strength properties tests were referred to the modulus of rupture, modulus of elasticity and tensile strength. Meanwhile, physical properties determination referred to basic density and moisture content. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…This farm consisting of acacia trees ( Acacia mangium ) that grow naturally in the forest with the land area is about two hectares. Acacia belongs to Fabaceae family and is called forest mangrove [59]. The bees collected the nectar mainly from Acacia mangium sap and flowers.…”
Section: Methodsmentioning
confidence: 99%
“…This farm consisting of acacia trees ( Acacia mangium ) that grow naturally in the forest with the land area is about two hectares. Acacia belongs to Fabaceae family and is called forest mangrove [59]. The bees collected the nectar mainly from Acacia mangium sap and flowers.…”
Section: Methodsmentioning
confidence: 99%
“…For example, Ismaili et al reported a basic density of 540 kg/m 3 for A. mangium grown in Malaysian Borneo. 25 Other studies have reported basic densities of 464 and 494 kg/m 3 for A. mangium grown in Malaysia. 26,27 The density of E. pellita grown at a plantation in Indonesian Borneo has been reported to vary from 556 to 652 kg/ m 3 .…”
Section: Acid Sulfite Cooking Experimentsmentioning
confidence: 94%
“…The constant loading speed was 0.6 mm/min. The shear parallel to the grain strength at maximum load was obtained using Equation (5).…”
Section: Shear Parallel To Grain Determinationmentioning
confidence: 99%
“…Jusoh et al [3] stated that these superbulk species have characteristics of a high growth rate, high volume, good stem form, and resistance to heart rot compared with the origin species. The Acacia mangium is a species of the family Leguminosae, which was introduced into Sabah in 1967 [4,5] and was also found in Queensland, Australia; Papua New Guinea; the Islands of Sula, Ceram, and Aru; and Irian Jaya [6]. The trees of this species are generally large and can grow to a height of 30 m with a straight bole [7].…”
Section: Introductionmentioning
confidence: 99%